Strategy Studies Tiered Value Chain By Samsung In The Era of Global Competition - Simanjuntak, Shimon (Talenta Publisher, 2024)
In the era of globalization, the smartphone industry has become one of the most competitive and dynamic sectors in the world. This paper aims to examine the tiered value chain as a strategy undertaken by Samsung with its suppliers in global market competition. This research uses descriptive qualitative research methods through literature studies from various sources relevant to the case study discussed. The result of this research is that Samsung chose to produce its own smartphones due to several factors. First, Samsung smartphone products have complex specifications, making it difficult for suppliers to produce them independently. Second, Samsung's smartphone products are difficult to codify, which means they are difficult to document and communicate clearly to suppliers. Third, the capability or ability of suppliers to produce smartphones that comply with Samsung's standards is considered low. Thus, the hierarchy value chain strategy implemented by Samsung in its smartphone production value chain aims to maintain control over the production process and maintain the quality of the products produced, so that it can compete effectively in the global market